2016
DOI: 10.1002/jctb.5017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NH4Br additive on mercury transformation and removal during CFB coal combustion

Abstract: BACKGROUND: Mercury emission from coal-fired power plants has caused widespread concern. Halogen is considered to be a good mercury oxidant and many researchers have added it into the coal for mercury removal. However, the mechanism of mercury transformation is still not clear. Effects of NH 4 Br additive on mercury transformation and removal were studied on a 6 kW th circulating fluidized bed (CFB) coal combustor. The main goal of this work is to explore in detail the mercury transformation mechanism in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…For Br 3d, a peak at around 67.8 eV was attributed to surface-bound HBr compounds and another peak at around 70.1 eV belonged to covalent Br (C–Br). ,, In comparison to the data from raw RHCBr0.5, it could be inferred that Br – turned into HBr after being exposed to the simulated oxy-fuel atmosphere with HCl. Zhao et al and Yang et al also found a similar phenomenon.…”
Section: Results and Discussionmentioning
confidence: 55%
“…For Br 3d, a peak at around 67.8 eV was attributed to surface-bound HBr compounds and another peak at around 70.1 eV belonged to covalent Br (C–Br). ,, In comparison to the data from raw RHCBr0.5, it could be inferred that Br – turned into HBr after being exposed to the simulated oxy-fuel atmosphere with HCl. Zhao et al and Yang et al also found a similar phenomenon.…”
Section: Results and Discussionmentioning
confidence: 55%
“…The proximate and ultimate analysis of the feeding coal was shown in Table . The mercury content in this type of coal is 62.84 ng/g, which is less than the mean value of coal in China (200 ng/g) . Besides, the chlorine content, which is regarded as the most important component influencing mercury oxidation, is 0.05% attributed to the low Cl content of coal .…”
Section: Experimental Methodologymentioning
confidence: 67%
“…The mercury content in this type of coal is 62.84 ng/g, which is less than the mean value of coal in China (200 ng/g). 25 Besides, the chlorine content, which is regarded as the most important component influencing mercury oxidation, is 0.05% attributed to the low Cl content of coal. 26 On the basis of the national coal classification standard of China (GB/T 5751-2009), the feeding coal is bituminous.…”
Section: Introductionmentioning
confidence: 99%
“…The thermodynamic studies also indicated that the process was spontaneous, feasible, and endothermic. Several other recent and relevant studies reported on mercury adsorption using different adsorbents are discussed …”
Section: Purification Of Mercury‐containing Wastewater Using Low‐costmentioning
confidence: 99%